Analisis Pengaruh Ukuran Perusahaan, Profitabilitas, Likuiditas Terhadap Struktur Modal pada Perusahaan Jasa Sektor Keuangan Perbankan yang Terdaftar di Bursa Efek Indonesia pada Tahun 2014 – 2018 - Natashia Natashia; Indra Widjaja (Universitas Tarumanagara, 2020)
An optimal capital structure is an important financial result because it increases the performance and value of a company. Good company performance on stock prices in the capital market, so that returns obtained by shareholders can be obtained optimally. In making decisions about companies consider several factors before choosing both internal and external namely: company size, profitability and liquidity. In this study, shows the size of the company, profitability and liquidity of the company's capital structure in 2014 - 2018